Two sinusoidal waves travel in the same direction with the same amplitude, wavelength, and speed. Their resultant wave function is given by: y(x,t) = Ares sin(kx-ωt+π/4). If Ares = 8 cm, then the amplitude, A, of each of the original sinusoidal waves producing this resultant wave is:
If two identical waves are traveling in the same direction, with the same frequency, wavelength and amplitude; BUT differ in phase the waves add together.
"y = y_1 + y_2" where
"y = A sin (kx - \u03c9t) \\space \\space and \\space \\space y_2 = A sin (kx - \u03c9t + \u03c6)"
"y = A sin(kx - \u03c9t) + A sin(kx - \u03c9t + \u03c6)"
Apply trig identity: "sin a + sin b = 2 cos((a-b)\/2) sin((a+b)\/2)"
"A sin ( a ) + A sin ( b ) = 2A cos((a-b)\/2) sin((a+b)\/2)"
"y = 2A cos (\u03c6 \/2) sin (kx - \u03c9t + \u03c6\/2)"
The resultant sinusoidal wave has the same frequency and wavelength as the original waves, but the amplitude has changed:
"Amplitude \\space equals \\space 2A cos (\u03c6 \/2)" with a phase angle of φ/2
here "\u03c6 = \\pi \/4"
Ares = "2A cos (\u03c6 \/2) = 2Acos(\\pi\/8)=8 cm \\to A = 4.32cm"
Comments
Leave a comment